2022
DOI: 10.3389/fcvm.2022.872102
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic endothelial sphingosine 1-phosphate receptor 1 enhances macrophage clearance via lymphatic system following myocardial infarction

Abstract: Lymphatic endothelial cell homeostasis plays important roles in normal physiological cardiac functions, and its dysfunction significantly influences pathological cardiac remodeling after myocardial infarction (MI). Our results revealed that sphingosine 1-phosphate receptor 1 (S1pr1) expression in cardiac lymphatic endothelial cells (LECs) was sharply changed after MI. It has been shown that S1pr1 tightly controlled LEC functions and homeostasis. We thus hypothesized that lymphatic endothelial S1pr1 might be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Indeed, immune cell recruitment by cardiac lymphatics, mediated by chemokines such as CCL21 (CC chemokine ligand) and CCL2, was recently shown to be modulated in LECs post-MI by the main S1P receptor S1PR1 (S1P receptor 1). 19 Overall, the immunomodulatory role of cardiac lymphatics appears somewhat similar as described previously in other tissues and in tumors. This immune-lymphatic interaction may depend, in part, on intercellular adhesion molecules such as Icam, Vcam, and LYVE1.…”
Section: Figure Cardiac Lymphatic Organization and Functionsupporting
confidence: 73%
“…Indeed, immune cell recruitment by cardiac lymphatics, mediated by chemokines such as CCL21 (CC chemokine ligand) and CCL2, was recently shown to be modulated in LECs post-MI by the main S1P receptor S1PR1 (S1P receptor 1). 19 Overall, the immunomodulatory role of cardiac lymphatics appears somewhat similar as described previously in other tissues and in tumors. This immune-lymphatic interaction may depend, in part, on intercellular adhesion molecules such as Icam, Vcam, and LYVE1.…”
Section: Figure Cardiac Lymphatic Organization and Functionsupporting
confidence: 73%
“…Future investigations can determine local S1P levels in lymphedema tissue to better evaluate the status of ligand production in this disease. A previous study demonstrated that LEC S1PR1 deficiency delays macrophage clearance after myocardial infarction, 88 and future assessments may prove a similar mechanism also operates in lymphedema pathogenesis.…”
Section: Discussionmentioning
confidence: 79%
“…S1PR1 is a G-protein-coupled receptor, expressed in lymphatic endothelial cells, and modulates immune cell transportation ( 34 ). In injured hearts, S1PR1/S1P activates downstream signals, including extracellular regulated protein kinases/chemokine ligand 2 (ERK), promoting lymphangiogenesis in the injured heart, driving macrophage trafficking, immune modulation, and cardiac repair after MI ( 35 , 36 ). Estrogen receptor α (ERα)/estrogen ligand plays a protective role in MI, associated with regulating lymphangiogenesis ( 37 ).…”
Section: Lymphangiogenesis and Cardiovascular Diseasementioning
confidence: 99%